Pecuniary emulation and invidious distinction: Signaling under behavioral diversity - Junichiro Ishida; Wing-chuen Suen (Osaka University, Institute of Social and Economic Research (ISER), 2023)
We introduce behavioral diversity to an otherwise standard signaling model, in which a fraction of agents choose their signaling actions according to an exogenous distribution. These behavioral agents provide opportunities for strategic low-type agents to successfully emulate higher types in equilibrium, which in turn reduces the cost for strategic high-type agents to separate from lower types. Behavioral diversity thus improves the equilibrium payoffs to all types of strategic agents. The model also exhibits a convergence property which is intuitively more appealing than the least-cost separating equilibrium of the standard setting.
Keywords: D82; Z13; 330; least-cost separating equilibrium; insensitivity to prior; behavioral diversity; equilibrium emulation